STUDI PEMIKIRAN SYAYKH PANJI GUMILANG TENTANG BUDAYA TOLERANSI DAN PERDAMAIAN DI MA'HAD AL-ZAYTUN: Analisis Pemikiran Syaykh Panji Gumilang Mengenai Toleransi Dan Perdamaian: Pendekatan Studi Pemikiran Islam - Vina Alfiyah; Riska Safriyanti; Santoso; Agus Rojak Samsuddin (Ikhtisar: Jurnal Pengetahuan Islam, 2025)
This study examines Syaykh Panji Gumilang’s thought on the concepts of tolerance and peace and their relevance to educational practices at Ma’had Al-Zaytun. The research employs a library-based qualitative approach using figure study methods and content analysis of written works, speeches, and institutional documents. The study is limited to a conceptual examination and does not evaluate the controversial aspects or socio-political practices related to the figure. The findings indicate that Syaykh Panji Gumilang’s ideas emphasize openness, respect for diversity, and the cultivation of a culture of peace within Islamic educational contexts. These concepts align with multicultural education theory, Johan Galtung’s positive peace framework, and the principles of maqasid al-shari‘ah. This study contributes to the enrichment of contemporary Islamic education literature, particularly concerning efforts to foster tolerance and peace within educational institutions.